High-frequency monitoring of the occurrence of preferential flow on hillslopes and its relationship with rainfall features, soil moisture and landscape. Issue 11 (18th August 2019) - Hu, Hongchang; Wen, Jie; Peng, Zhenyang; Tian, Fuqiang; Tie, Qiang; Lu, You; Khan, Mohd Yawar Ali
ABSTRACT: High-frequency monitoring was conducted to quantify the frequency and controlling factors of preferential flow (PF) in a monsoon-influenced sub-humid mountainous catchment (6.48 km 2 ) of Northern China. Rainfall was measured using nine bucket raingauges. Soil moisture probes were set up at 12 sites to observe the PF. Overall, 129 rainfall events were identified during the years 2014–2016. The average PF occurrence was 41%, which increased to 71% during heavy rainfall events (>20 mm) revealing a strong influence of the amount and intensity of rainfall. The study also revealed that the PF increased with antecedent soil moisture. Soil moisture was much higher on flat sites compared to sloping sites, providing evidence that the topography has a strong influence on rainfall infiltration and runoff which, subsequently, influence soil moisture variation and the occurrence of PF. Our findings provide valuable insights into the hydrological processes for studies in regions with similar environmental conditions.